INVESTIGATING ENGLISH DEPARTMENT STUDENTS’ FOREIGN LANGUAGE SPEAKING ANXIETY: A CASE STUDY IN UNIVERSITAS AIRLANGGA, INDONESIA - Dyas Intan Rachmawati; Jurianto Jurianto (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
Anxiety during a speaking performance is a common phenomenon experienced by any EFL learners, including students majoring in English. Focusing on the issue, this study investigates the correlation between students’ foreign language speaking anxiety and speaking achievement. Moreover, this study also observes the levels and the sources of the speaking anxiety among the English Department’s fifth-semester students of Universitas Airlangga. This study used the Foreign Language Speaking Anxiety Scale (FLSAS) by Öztürk and Gurbuz (2014). The FLSAS questionnaire was distributed to 114 students in order to explore the correlation between speaking anxiety and speaking achievement, the speaking anxiety levels, and the speaking anxiety sources. The data collected through questionnaire were analyzed with SPSS 25.0. Pearson Product Moment Correlation isused to determine the correlation, while descriptive statistic alanalys is isused to investigate the levels and the sources for speaking anxiety. Horwitz, Horwitzand Cope’s(1986) theory and Horwitz and Young (1991) about the source and the levels of foreign language speaking anxiety are also used in this study. This study found that there is a significant negative correlation between speaking anxiety levels and speaking achievement. This means the higher the speaking anxiety they experience, the lower the achievement score they get. Most of the students have moderate levels of speaking anxiety, which is mainly due to the fear of negative evaluation.This study indicates that although the EFL learners are often exposed to English, they still experience speaking anxiety. These findings suggest that the lecturers should be more aware of students’ anxiety and use strategies that might encourage the students to speak more confidently.